Nachträge zur Edition einer syrischen ṭaḇliṯo in Aethiopica 24 (Bausi und Desreumaux 2021) - Waltisberg, Michael (Aethiopica, 2022)
The following short note offers some comments and corrections on the first edition of a Syriac ṭaḇliṯo published in Aethiopica 24 (Bausi and Desreumaux 2021). It particularly focuses on a few issues of the reading of the text, the transcription of Syriac, and the date.